Establishment of Callus and Cell Suspension Cultures of Helicteres isora L. - Shaikh, Samrin; Shriram, Varsha; Vinay Kumar, Tushar Khare and (Research in Plant Biology)
Helicteres isora L. (Malvaceae) is a medicinal plant highly used in traditional therapeutic practices. It has shown wide-spectrum therapeutic activities including anti-plasmodial, hypoglycemic, hypolipidemic, hepatoprotective, antinociceptive, antioxidant and anti-HIV. Present investigation was undertaken with an objective of establishment of cell suspension cultures of this plant which can be further used for in vitro production of desired secondary metabolites and their further scale-up. Seed dormancy was broken using sulfuric acid and seedlings were raised in vitro. MS medium supplemented with 2,4-D (0.5 mg/L) produced maximum callus from the nodal explants. The callus produced was used as an explant for the establishment of suspension cultures. MS medium without any supplement was proved best for the establishment of cell suspension cultures of H. isora. To the best of our knowledge, this is the first report on H. isora cell suspension culture establishment.